INVESTIGATING THE RELATIONSHIP BETWEEN CULTURAL INTELLIGENCE AND STUDENT’S LISTENING COMPREHENSION - Dewi, Desi Surlitasari; Wilany, Eka; Sidabutar, Isak Steven; Ria, Tiara Nove (FKIP - Universitas Tanjungpura, 2022)
Student’s listening comprehension could be affected by several factors, one of the factors is student’s cultural intelligence. It is an ability to grasp and reason correctly any problem as education, government, business, and academic research. This study aimed to find out the correlation between students’ cultural intelligence and their listening comprehension at first semester students of English Department Universitas Riau Kepulauan in the academic year of 2020/2021. The data of the research were students’ cultural intelligence scores derived from cultural intelligence scale and student’s listening comprehension from IELTS listening tests. The population of the research were 28 students of first semester of English Department of Universitas Riau Kepulauan. Before testing the hypothesis, a normality test was conducted by using saphiro wilk to ensure that the data were in normal distribution. The data of cultural intelligence had a significance value of 0.397 and 0.372 for listening comprehension which is bigger than 0.05 with the degree of freedom 28. Therefore, it can be concluded that the data of listening comprehension and cultural intelligence were normal. After conducting the hypothesis, it was found out that rcalculated(0.217) is lower than rtable(0.374). The finding of the study concluded that there was no significant correlation between students’ cultural intelligence and students’ listening comprehension. However, the positive correlation implied that possessing higher cultural intelligence might be beneficial for student’s listening comprehension.